Implications of an Incidental Pulmonary Arteriovenous Malformation - Van K. Holden MD; Nirav G. Shah MD; Avelino C. Verceles MD, MS (SAGE Publishing, 2016)
Introduction. Pulmonary arteriovenous malformations (PAVMs) have been associated with life-threatening complications, such as stroke and massive hemoptysis, thus posing significant morbidity if left untreated. We report a case of an incidental finding of a PAVM in a trauma patient newly recognized to have suspected hereditary hemorrhagic telangiectasia (HHT). Case Description. A 34-year-old man with a history of recurrent epistaxis presented with a sudden fall associated with seizure-like activity. Trauma imaging showed a large subdural hematoma and, incidentally, a serpiginous focus within the right upper lobe with a prominent feeding artery consistent with a PAVM. The patient was diagnosed with a simple PAVM related to possible or suspected HHT, an autosomal dominant trait with age-related penetrance. He underwent a pulmonary arteriography of the right upper and lower lobe with the use of a microcatheter system; however, the PAVM could not be visualized. Thus, he was managed medically. The patient was educated on the need for prophylactic antibiotics prior to dental procedures and surveillance imaging. Discussion. Our case highlights the importance of obtaining a complete past medical and family history in young patients with a history of recurrent epistaxis to elicit features of HHT. The diagnosis can be made clinically and directly affects family members, who would otherwise not receive appropriate screening.